A multi-target therapeutic strategy: The efficacy of coffea canephora husk extract in mitigating oxidative stress, infection, and inflammation – a systematic review - Kamilah, Rona Hawa; Palungan, Juliana (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Robusta coffee (Coffea canephora) husk is a massive agro-industrial by-product. Despite possessing a rich phytochemical profile superior to Arabica, it remains underutilized as environmental waste. This review explores its valorization from a pollutant into a functional pharmaceutical resource. Purpose: To synthesize evidence regarding the bioactive potential of Robusta husk as a "natural shield" against oxidative stress and infections, and assess its feasibility in pharmaceutical formulation development. Method: Following PRISMA 2020 guidelines, a search of PubMed, ScienceDirect, and Google Scholar (2020–2026) identified 17 eligible studies. These included in vitro, in vivo, and formulation research selected for synthesis. Results: Robusta husk is exceptionally rich in caffeine and chlorogenic acids. It exhibits potent antioxidant activity (IC50<50 ppm) and antimicrobial efficacy against Enterococcus faecalis, Porphyromonas gingivalis, and Staphylococcus aureus. In vivo studies further confirm anti-inflammatory and wound-healing acceleration. Technically, the extract has been successfully formulated into stable antioxidant gels, lotions, and peel-off masks. Conclusion: C. canephora husk acts as a promising multi-target therapeutic agent. Future research must prioritize standardization and clinical trials to facilitate its translation into standardized herbal medicines.